Technology Use and Attitudes in Music Learning - Waddell, George; Williamon, Aaron (Frontiers in ICT, 2019)
While the expansion of technologies into the music education classroom has been studied in great depth, there is a lack of published literature regarding the use of digital technologies by students learning via one-to-one instrumental music instruction frameworks. Do musicians take their technology use into the practice room and teacher’s studio, or does the traditional nature of the master-apprentice teaching model promote differing attitudes of musicians toward their use of technology in learning their instrument? The present study examined (1) musicians’ skills with and attitudes toward technologies in their day-to-day lives, (2) how they engage with technology in the learning of musical instruments, (3) how their attitudes as music learners differ from their role as music teachers, and (4) musicians’ attitudes toward potential new technologies and what factors predict adoption of new tools. To investigate these issues, we developed the Technology Use and Attitudes in Music Learning Survey, which included adaptations of Davis’ 1989 scales for Perceived Usefulness and Perceived Ease of Use of Technology. Data were collected from an international cohort of 338 amateur, student, and professional musicians ranging widely in age, instrument, and musical experience. Results showed a generally positive attitude towards current and future technology use among musicians and supported the Technology Acceptance Model (TAM), wherein technology use in music learning was predicted by perceived ease of use via perceived usefulness, although technology use itself, age, and musical experience did not predict hypothetical future use. Musicians’ self-perceived skills with smartphones, laptops, and desktop computers was found to surpass traditional audio and video recording devices regardless of demographics, and the majority of musicians reported using the classic musical technologies of metronomes and tuners on smartphones and tablets rather than bespoke devices. Despite this comfort with and access to new technology, its reported availability within lesson spaces was half of that within practice spaces, and while a large percentage of musicians actively record their playing, these recordings are reviewed with significantly less frequency. These results highlight opportunities for technology to take a greater role in improving music learning through enhanced student-teacher interaction and self-regulated learning.